Evolution of human papilloma virus prevalence in a highly vaccinated region in Belgium: a retrospective cohort study in Flemish women (2010–2019). Issue 1 (25th May 2022) - Huyghe, Evelyne; Abrams, Steven; Bogers, John-Paul; Verhoeven, Veronique; Benoy, Ina
Abstract : Objective: In order to lower the incidence of cervical cancer, vaccines against high-risk types of the human papilloma virus (hrHPV) were approved and brought on the market in 2007, with a partial reimbursement for Belgian citizens younger than 18 years old. Since 2010, a school-based vaccination program ensures a high vaccination coverage in young women. In this study, the impact of the Belgian vaccination program on the prevalence of HPV 16/18 is studied, together with the evolution of the prevalence of other hrHPV types and precancerous lesions. Methods: Results of HPV typing and cytology in papanicolaou-smears from women aged 20–23 years taken between 2010 and 2019 were used. An older, nonvaccinated group of women of 40–45 years old served as a control group. Results: A significant decrease in prevalence of HPV types 16 and 18 was found in the 20–23-years-old women, whereas no decrease was found in the age group 40–45. Alongside this decrease, a significant decrease in prevalence of subtypes 6, 11 and 31 was observed, whereas type 31 is not included in the administered vaccines. Remarkably, there was no decrease in prevalence of cytological abnormalities in the study group during this study. There was even an increase in prevalence of high-risk types 53, 58 and 67. Conclusion: These findings emphasise the need to maintain the screening programs, even in areas with high vaccination coverage.